Husband’s Education Level and Alcohol Drinking Habit as Risk Factors of HIV Infection among Housewives in Pati District - Aeni, Nurul; Westendorp, Annemarie (UI Scholars Hub, 2017)
Cases of Human Immunodeficiency Virus (HIV) infection in Pati District increase, particularly among housewives. The aim of this study was to analyse the risk factors of HIV infection among housewives in Pati District using case-control study design. The respondents were 90 housewives divided into case and control group. The case group consisted of 30 housewives living with HIV, while the control group comprised 60 housewives living in the similar area of the counterparts. The data collection was focused on demographic, sexual behaviour, and sociocultural variables possessed by housewives and their husbands. The study resulted that the risk factors of HIV infection among housewives based on bivariate analysis were housewife’s level of education, husband’s level of education, husband’s occupation, housewife’s sexual transmission disease (STD) record, husband’s STD record, husband’s participation in religious activities, and husband’s alcohol drinking habit. The risk factors that fitted to logistic regression model were education level and alcoholic behaviour of husbands that contributed to 29.1% HIV infection among housewives. In conclusion, the husband’s variables are proved having stronger and very significant correlation with HIV infection among housewives than housewife’s variables.